2017
DOI: 10.5604/12303666.1227885
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Comfort Properties of Bi-layer Knitted Fabric structure for Volleyball Sportswear

Abstract: The thermal comfort properties of different knitted fabric structures made from modal, polypropylene and micro denier polyester were studied for volleyball sportswear. Eleven knitted fabrics were produced, in which three samples were single jersey, two plated and six bi-layer knitted structures. The air permeability, water vapour permeability, thermal conductivity, wicking and drying ability of bi-layer knitted fabric made up of polypropylene as the inner layer and modal as the outer layer with one tuck point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…In support of this aim, many studies have focussed on double-face structures to achieve high level of comfort [19–23]. The performance of layered fabric in thermo-physiological regulation is better than single layer textile structure [24–27]. Layering of fabrics used as garment has major effect on properties such as thermal conductivity, air permeability and moisture vapour transmittance [28].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this aim, many studies have focussed on double-face structures to achieve high level of comfort [19–23]. The performance of layered fabric in thermo-physiological regulation is better than single layer textile structure [24–27]. Layering of fabrics used as garment has major effect on properties such as thermal conductivity, air permeability and moisture vapour transmittance [28].…”
Section: Introductionmentioning
confidence: 99%
“…When fabric is subjected to heavy sweating conditions, not all the sweat absorbed by fabric can be given off to the atmosphere instantaneously. Thus to prevent the wearer from feeling wet and clammy [17], the sweat should be transported away from the skin surface body. The transportation of sweat may be in the form of liquid or vapor so that the fabric touching the skin feels dry [11,15].…”
Section: • Heat Transfer By Respirationmentioning
confidence: 99%
“…Mallikarjunan et al [7] studied the comfort and thermophysiological characteristics of multilayered fabrics with various woven and knitted fabric combination by using cotton, lyocell, polyester and polypropylene and found that C/PP plaited fabric and cotton/polyester plaited fabric show better results for air permeability, thermal conductivity, water absorbency, water spreading rate, water vapour permeability and wickability suitable for cold climatic conditions. Suganthi et al [8] studied the thermal comfort properties of bi-layer knitted fabric structure for volleyball sportswear and found that bi-layer knitted fabric made with polypropylene as inner layer has better moisture transfer characteristics compared to plated and single jersey structure. Suganthi and Senthilkumar [9] studied the moisture management properties of bilayer knitted fabrics for sportswear and found that the micro-fibre polyester and modal bi-layer knitted fabric show better results for moisture management property.…”
Section: Introductionmentioning
confidence: 99%
“…Sakthi et al [13] studied the development of double layer knitted fabric for sportswear using tencel/ polypropylene fibres and found that this combination showed better results for comfort characteristics and well suited for sportswear application. Suganthi et al [14] studied the thermal comfort properties of bi-layer knitted fabric structure for volleyball sportswear and found that bi-layer knitted fabric made with polypropylene as inner layer had better moisture transfer characteristics when compared with plated and single jersey structure. In our present work, we have studied the effect of polypropylene, polyester, acrylic and nylon yarns as inner layer and cotton yarn as outer layer on moisture transfer characteristics of double-face knitted fabrics.…”
Section: Introductionmentioning
confidence: 99%